Perception of service using AMSS technology, information system in Educational Area 2, Ratchaburi Province - Intarangkun Na Ayudhya, Pathomporn; Khumsamart , Supattarasak; Heedjan, Punya (Journal of Modern Learning Development, 2022)
The objectives of this study were 1. To study the use of AMSS technology system, information system in Educational Area 2, Ratchaburi Province 2. To study the process of perception of service usage of AMSS technology system, information system in Educational Area 2, Ratchaburi Province and 3. to be Guidelines for the development of services using AMSS technology, information systems in Educational Area 2, Ratchaburi Province which is an exploratory research A questionnaire was used to collect data for 400 people. The survey respondents found that the most females, aged 20-40 years, studied at a bachelor's degree in academic position. and use the service 10-20 times The results of the analysis of opinions about the components of the use of AMSS technology found that the opinions were at a high level (= 3.90, SD. = 0.44). The opinions were at a high level (= 4.06, SD. = 0.62). The results of the analysis of the process of perception of service using AMSS technology found that the process of perception of service of using AMSS technology (overall) found that the opinions were at a high level (= 3.82, SD. = 0.47) found that the observation The opinions were at a high level (= 4.01, SD. = 0.65). Research hypotheses on individual fundamental factors affecting the process of perceived services using AMSS technology found that overall, there was no statistically significant difference at the .05 level. Through the use of AMSS technology, personnel and service users have developed more modern information technology and communication processes. This can be integrated for more system development.